Rare-Earth Doping in Nanostructured Inorganic Materials - Zheng, Bingzhu; Fan, Jingyue; Chen, Bing; Qin, Xian; Wang, Juan; Wang, Feng; Deng, Renren; Liu, Xiaogang (Chemical reviews, 2022)
Impurity doping is a promising method to impart new properties to various materials. Due to their unique optical, magnetic, and electrical properties, rare-earth ions have been extensively explored as active dopants in inorganic crystal lattices since the 18th century. Rare-earth doping can alter the crystallographic phase, morphology, and size, leading to tunable optical responses of doped nanomaterials. Moreover, rare-earth doping can control the ultimate electronic and catalytic performance of doped nanomaterials in a tunable and scalable manner, enabling significant improvements in energy harvesting and conversion. A better understanding of the critical role of rare-earth doping is a prerequisite for the development of an extensive repertoire of functional nanomaterials for practical applications. In this review, we highlight recent advances in rare-earth doping in inorganic nanomaterials and the associated applications in many fields. This review covers the key criteria for rare-earth doping, including basic electronic structures, lattice environments, and doping strategies, as well as fundamental design principles that enhance the electrical, optical, catalytic, and magnetic properties of the material. We also discuss future research directions and challenges in controlling rare-earth doping for new applications.